Educational Pattern of Gifted Children from the Perspective of the Qur’an (Study of QS. Ali ‘Imrān Verse 159 and QS. Al Isrā Verse 84) - Nafisah, Is Is Saidah; Badruzzaman, Dimyati; Slamet, M. Ubaidillah Al-Ghifary (YASIN, 2025)
Many people still do not understand that gifted children are children who have good strengths and have a positive impact on the people around them. For this reason, this study aims to reveal the pattern of gifted children's education from the Quran perspective in QS. Ali Imran verse 159 and QS Al Isra' verse 84. This study is library research with data collection from primary and secondary sources. The study results showed that in the interpretation of Al Misbah by M. Quraish Shihab and Tafsir Al Azhar by Buya Hamka, every human being has a tendency, potential, and innate that encourage his activities to work and develop talents, including intelligent children with unique talents (gifted). According to the two interpretations, the way parents nurture gifted children must take four steps: being gentle with children, forgiving if children make mistakes, inviting deliberation if children want something, and having faith in God through prayer and other worship.